Oxygen-enhanced MRI MOLLI T1 mapping during chemoradiotherapy in anal squamous cell carcinoma. (May 2020) - Bluemke, Emma; Bulte, Daniel; Bertrand, Ambre; George, Ben; Cooke, Rosie; Chu, Kwun-Ye; Durrant, Lisa; Goh, Vicky; Jacobs, Clare; Ng, Stasya M.; Strauss, Victoria Y.; Hawkins, Maria A.; et al.
Highlights: Oxygen-enhanced MRI and T1-mapping explored as prognostic radiotherapy biomarker. Significant increase in tumour T1 across patients following chemoradiotherapy. Before chemoradiotherapy, OE-MRI showed no significant changes in tumour T1. After chemoradiotherapy, OE-MRI showed a significant decrease in tumour T1. T1 changes from oxygen-enhanced MRI could indicate change in tumour perfusion. Abstract: Background and purpose: Oxygen-enhanced magnetic resonance imaging (MRI) and T1-mapping was used to explore its effectiveness as a prognostic imaging biomarker for chemoradiotherapy outcome in anal squamous cell carcinoma. Materials and methods: T2-weighted, T1 mapping, and oxygen-enhanced T1 maps were acquired before and after 8–10 fractions of chemoradiotherapy and examined whether the oxygen-enhanced MRI response relates to clinical outcome. Patient response to treatment was assessed 3 months following completion of chemoradiotherapy. A mean T1 was extracted from manually segmented tumour regions of interest and a paired two-tailed t -test was used to compare changes across the patient population. Regions of subcutaneous fat and muscle tissue were examined as control ROIs. Results: There was a significant increase in T1 of the tumour ROIs across patients following the 8–10 fractions of chemoradiotherapy (paired t -test, p < 0.001, n = 7). At baseline, prior to receiving chemoradiotherapy, there were no significant changes in T1 across patients from breathing oxygen (n = 9). In the post-chemoRT scans (8–10 fractions), there was a significant decrease in T1 of the tumour ROIs across patients when breathing 100% oxygen (paired t -test, p < 0.001, n = 8). Out of the 12 patients from which we successfully acquired a visit 1 T1-map, only 1 patient did not respond to treatment, therefore, we cannot correlate these results with clinical outcome. Conclusions: These clinical data demonstrate feasibility and potential for T1-mapping and oxygen enhanced T1-mapping to indicate perfusion or treatment response in tumours of this nature. These data show promise for future work with a larger cohort containing more non-responders, which would allow us to relate these measurements to clinical outcome.